THE Age, Education and Income Levels As Demographic Determinants of Retirement Planning of Public Health Sector Employees in Ngororero District, Rwanda - J. C, Bizimana; A. A., Ogbe, (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aimed to assess the effects of age, education and income levels as determinants of retirement planning of public health sector employees in Ngororero District. The theoretical review of this research suggests that the wealth of a nation is distributed in such a way that the younger households have little wealth, the middle-aged households have relatively more wealth and the most wealth is secured by households immediately before their retirement. This study was conducted through quantitative and qualitative approaches employing descriptive survey design. The target population consisted of 487 employees working in Public Health Sector in Ngororero District. The sample size is composed of 108 respondents for questionnaire items and interview schedule. The sampling techniques consisted of stratified sampling, simple random sampling and purposive sampling. The data have been collected using questionnaires and interview schedules. The validity has been established and the reliability of the data was tested. The data have been analyzed through descriptive analysis. Spearman’s Rank Correlation Coefficient was used to establish the relationship between independent and dependent variables. Analysis of Variance (ANOVA) technique was used to test the hypotheses (p≤ 0.05). This study found that age, education and income levels have a strong positive correlation with retirement planning of public health sector employees in Ngororero District (Correlation Coefficient is above 0.99). They also have a significant effect on retirement planning of public health sector employees in Ngororero District. Exception is for gender which does not have a significant effect of retirement planning.  The study concluded that age, education and income levels have a great effect on retirement planning of employees as it impacts of their retirement decisions. The study recommended the necessity of encouraging people to plan for retirement at early stage so that they secure welfare at old age. Social Security Organizations should design specific programs meant to increase the level of awareness of retirement saving schemes in public health sector. The Local Government and Private Sector should embrace investment opportunities and development projects meant to increase the level of income of the population.